Effects of 20 mg oral Δ9‐tetrahydrocannabinol on the olfactory function of healthy volunteers1. (November 2014) - Walter, Carmen; Oertel, Bruno G.; Ludyga, Dagmar; Ultsch, Alfred; Hummel, Thomas; Lötsch, Jörn
<x xml:space="preserve">Abstract</x> Aims Olfactory loss impairs the patient's quality of life. In individualized therapies, olfactory drug effects gain clinical importance. Molecular evidence suggests that among drugs with potential olfactory effects is Δ9‐tetrahydrocannabinol (THC), which is approved for several indications, including neuropathic pain or analgesia in cancer patients. The present study aimed at assessing the olfactory effects of THC to be expected during analgesic treatment. Methods The effects of 20 mg oral THC on olfaction were assessed in a placebo‐controlled, randomized cross‐over study in healthy volunteers. Using an established olfactory test (Sniffin' Sticks), olfactory thresholds, odour discrimination and odour identification were assessed in 15 subjects at baseline and 2 h after THC administration. Results Δ9‐Tetrahydrocannabinol impaired the performance of subjects (n = 15) in the olfactory test. Specifically, olfactory thresholds were increased and odour discrimination performance was reduced. This resulted in a significant drop in composite threshold, discrimination, identification (TDI) olfactory score by 5.5 points (from 37.7 ± 4.2 to 32.2 ± 5.6, 95% confidence interval for differences THC vs. placebo, −7.8 to −2.0, P = 0.003), which is known to be a subjectively perceptible impairment of olfactory function. Conclusions Considering the resurgence of THC in medical use for several pathological conditions, the present results indicate that THC‐based analgesics may be accompanied by subjectively noticeable reductions in olfactory acuity. In particular, for patients relying on their sense of smell, this might be relevant information for personalized therapy strategies.